Symmetry Breaking and Electrical Frustration during Tip-Induced Polarization Switching in the Nonpolar Cut of Lithium Niobate Single Crystals - Ievlev, Anton V.
Polarization switching in ferroelectric materials is governed by a delicate interplay between bulk polarization dynamics and screening processes at surfaces and domain walls. Here we explore the mechanism of tip-induced polarization switching at nonpolar cuts of uniaxial ferroelectrics. In this case, the in-plane component of the polarization vector switches, allowing for detailed observations of the resultant domain morphologies. We observe a surprising variability of resultant domain morphologies stemming from a fundamental instability of the formed charged domain wall and associated electric frustration. In particular, we demonstrate that controlling the vertical tip position allows the polarity of the switching to be controlled. This represents a very unusual form of symmetry breaking where mechanical motion in the vertical direction controls the lateral domain growth. The implication of these studies for ferroelectric devices and domain wall electronics are discussed.